Characteristics of the Ahmadabad hematite/barite deposit, Iran – studies of mineralogy, geochemistry and fluid inclusions - Babaei, Amir Haji; Ganji, Alireza (Instytut Geologii UAM, 2018)
The Ahmadabad hematite/barite deposit is located to the northeast of the city of Semnan, Iran. Geostructurally, this deposit lies between the Alborz and the Central Iran zones in the Semnan Subzone. Hematite-barite mineralisation occurs in the form of a vein along a local fault within Eocene volcanic host rocks. The Ahmadabad deposit has a simple mineralogy, of which hematite and barite are the main constituents, followed by pyrite and Fe-oxyhydroxides such as limonite and goethite. Based on textural relationships between the above-mentioned principal minerals, it could be deduced that there are three hydrothermal mineralisation stages in which pyrite, hematite and barite with primary open space filling textures formed under different hydrothermal conditions. Subsequently, in the supergene stage, goethite and limonite minerals with secondary replacement textures formed under oxidation surficial conditions. Mi- crothermometric studies on barite samples show that homogenisation temperatures (T H ) for primary fluid inclusions range from 142 to 256°C with a temperature peak between 200 and 220°C. Salinities vary from 3.62 to 16.70 NaCl wt% with two different peaks, including one of 6 to 8 NaCl wt% and another of 12 to 14 NaCl wt%. This indicates that two different hydrothermal waters, including basinal and sea waters, could have been involved in barite mineralisation. The geochemistry of the major and trace elements in the samples studied indicate a hydrothermal origin for hematite and barite mineralisation. Moreover, the Fe/Mn ratio (>10) and plots of hematite samples of Ahmadabad ores on Al-Fe-Mn, Fe-Mn-(Ni+Co+ Cu)×10, Fe-Mn-SiX 2 and MnO/TiO 2 – Fe 2 O 3 /TiO 2 diagrams indicate that hematite mineralisation in the Ahmadabad deposit occurred under hydrothermal conditions. Furthermore, Ba and Sr enrichment, along with Pb, Zn, Hg, Cu and Sb depletion, in the barite samples of Ahmadabad ores are indicative of a low temperature hydrothermal origin for the deposit. A comparison of the ratios of La N /Yb N , Ce N /Yb N , Tb N /La N , Sm N /Nd N and parameters of Ce/Ce* and La/La* anomalies of the hematite, barite, host volcanic rocks and quartz latite samples to each other elucidate two important points: 1) the barite could have originated from volcanic host rocks, 2) the hematite could have originated from a quartz latite lithological unit. The chondrite normalised REE patterns of samples of hematite barite, volcanic host rocks and quartz latite imply that two different hydrothermal fluids could be proposed for hematite and barite miner- alisation. The comparison between chondrite normalised REE patterns of Ahmadabad barite with oceanic origin barite and low temperature hydrothermal barite shows close similarities to the low temperature hydrothermal barite deposits.
Keywords: geochemistry; trace and rare earth elements; Semnan